Physiological Ecology of Winter Hibernation by the High-Altitude Frog Nanorana parkeri - Niu, Yonggang; Chen, Qiang; Storey, Kenneth B.; Teng, Linhong; Li, Xiangyong; Xu, Tisen; Zhang, Haiying (Physiological and biochemical zoology, 2022)
The Xizang plateau frog, Nanorana parkeri (Anura: Dicroglossidae), enters a dormant state in the winter in response to seasonal cold and lack of food. To investigate the physiological and ecological characteristics of overwintering in this species, we measured habitat conditions (hibernacula temperatures, body temperature, and water quality variables), morphology, metabolite concentrations, total antioxidant capacity (T-AOC), and bacteria-killing ability (BKA) of plasma during summer and winter. We found that N. parkeri hibernates underwater at the bottom of ponds (10–20-cm depth). Dissolved oxygen content in the water decreases significantly (by 12%) in the winter compared with summer, suggesting that overwintering N. parkeri may experience hypoxia. Body mass, body mass index, hepatosomatic index, and hepatic glycogen concentration all increased significantly in winter-collected frogs as compared to summer-collected individuals, indicating that overwintering N. parkeri accumulates high fuel/energy reserves to support prolonged periods of hibernation. A significant reduction in glucose, urea, and lactate concentrations in most organs may be closely related to metabolic depression in overwintering N. parkeri. Liver lactate concentration rose significantly in winter-collected frogs, suggesting that anaerobic metabolism dominates when this species overwinters. The T-AOC of plasma showed a significant reduction in winter, suggesting a reduced need for antioxidant defenses. Oppositely, the BKA of plasma increased significantly in winter versus summer, indicating that innate immunity was enhanced during overwintering. In summary, these behavioral (migrating to caves), physiological, and biochemical adjustments may be key for the successful overwintering of this high-altitude frog.